2012
DOI: 10.1096/fj.11-201061
|View full text |Cite
|
Sign up to set email alerts
|

CD137 on inflamed lymphatic endothelial cells enhances CCL21‐guided migration of dendritic cells

Abstract: CD137/TNFR9/41BB was originally described as a surface molecule present on activated T and NK cells. However, its expression is broader among leukocytes, and it is also detected on hypoxic endothelial cells and inflamed blood vessels, as well as in atherosclerotic lesions. Here, we demonstrate that lymphatic endothelial cells (LECs) up-regulate CD137 expression from undetectable baseline levels on stimulation with TNF-α, LPS, and IL-1β. CD137 cross-linking with an agonistic mAb results in NF-κB nuclear translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…Notch inhibition (Fig. 5B) also led to increased expression of inflammatory markers and regulators ( ptgs2b, pde7a, sgpl1) (Smith et al, 2003;Ogryzko et al, 2014) and the pro-inflammatory endothelial genes arg2 (Ryoo et al, 2008) and tnfrsf9a (CD137) (Olofsson et al, 2008;Teijeira et al, 2012) (Fig. 5B).…”
Section: Decreased Notch Signalling Affects Endothelial Cardiovasculmentioning
confidence: 90%
See 1 more Smart Citation
“…Notch inhibition (Fig. 5B) also led to increased expression of inflammatory markers and regulators ( ptgs2b, pde7a, sgpl1) (Smith et al, 2003;Ogryzko et al, 2014) and the pro-inflammatory endothelial genes arg2 (Ryoo et al, 2008) and tnfrsf9a (CD137) (Olofsson et al, 2008;Teijeira et al, 2012) (Fig. 5B).…”
Section: Decreased Notch Signalling Affects Endothelial Cardiovasculmentioning
confidence: 90%
“…Also, Notch signalling abrogation resulted in increased wound-related endothelial and inflammatory gene expression and an increased abundance of macrophages. This anti-inflammatory role of Notch might be direct, by regulating endothelial inflammatory genes such as tnfrsf9a (Olofsson et al, 2008;Teijeira et al, 2012), or might be linked to the appearance and maturation of the endocardium upon Notch inhibition. Cardiac injury induces the dedifferentiation and proliferation of existing cardiomyocytes, which peaks at 7 dpci (Kikuchi et al, 2010;Sallin et al, 2014;Bednarek et al, 2015), and endocardial signals are implicated in this process Zhao et al, 2014).…”
Section: Signals Controlling Endocardial Dynamicsmentioning
confidence: 99%
“…T lymphocytes were costimulated with recombinant with plate-bound anti-CD3ε (0.5 μg/mL, clone OKT3) and anti-CD137 (10 μg/ml, clone 6B4 or urelumab) or the respective isotype control antibodies at 2. cells/mL for 72 h in complete media. In some experiments plate bound anti CD3 (0.5 μg/mL) and 4-1BBL or GAG protein coated beads (ratio 1.2) were used (27). In some experiments, CD8 + + T cells were additionally costimulated with plate-bound anti-CD28 (10 μg/mL, 37.51) in the presence or absence of anti-CD137.…”
Section: In Vitro Cd8 + T-lymphocyte Costimulation Assaymentioning
confidence: 99%
“…Also, lymphatic endothelial cell proliferation during acute inflammation is governed not only by VEGF-C and VEGF-D action through VEGFR-3 but also by other factors as FGF-2, PLGF-2, HGF, EGF, and KC/CXCL17 (Lachance et al 2013). Recently, Teijeira et al (2012) demonstrated that CD137 marker, originally described as a surface molecule present in activated T and NK cells, was upregulated in lymphatic endothelial cells on stimulation with TNF-a, lipopolysaccharide, and IL-1b. Tissue inflammation modulates gene expression of lymphatic endothelial cells and dendritic cell migration in a stimulus-dependent manner by Prox-1, VEGFR-3, and LYVE-1 significant downregulation following contact hypersensitivity (Vigl et al 2011).…”
Section: Lymphatic Endothelial Cellsmentioning
confidence: 99%